2015
DOI: 10.1111/andr.12119
|View full text |Cite
|
Sign up to set email alerts
|

Male fertility following spinal cord injury: an update

Abstract: SUMMARYSpinal cord injury (SCI) occurs most often in young men at the peak of their reproductive health. The majority of men with SCI cannot father children naturally. Three major complications contribute to infertility in men with SCI: erectile dysfunction, ejaculatory dysfunction, and abnormal semen quality. Erectile dysfunction can be managed by regimens available to the general population, including oral administration of phosphodiesterase-5 (PDE-5) inhibitors, intracavernosal injections, vacuum devices, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 123 publications
0
81
0
2
Order By: Relevance
“…9 This was borne out in our study, where over 70% of patients were unable to ejaculate. Successful methods to produce antegrade ejaculation include penile vibratory stimulation and electro-ejaculation.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…9 This was borne out in our study, where over 70% of patients were unable to ejaculate. Successful methods to produce antegrade ejaculation include penile vibratory stimulation and electro-ejaculation.…”
Section: Discussionmentioning
confidence: 60%
“…[6][7][8] Advances in medicine have increased the options for treatment of sexual dysfunction and infertility in men with SCI. 9 Oral phosphodiesterase inhibitors, such as sildenafil are highly efficacious in the treatment of ED in SCI. 10 Interventions to induce ejaculation have a success rate of 95% and pooled analyses reveal a pregnancy rate after advanced fertility treatments of 51%.…”
Section: Introductionmentioning
confidence: 99%
“…There are 3 common sequelae of SCI that impact fertility: erectile dysfunction, ejaculatory dysfunction, and abnormal semen quality. 9 Techniques to help achieve improved erections and ejaculation, coupled with advances in assisted reproductive technologies, have made fathering biologic children a reality for men living with SCI.…”
Section: Fertilitymentioning
confidence: 99%
“…Chronic urinary tract infection could be the most plausible cause, because infiltrating leukocytes secrete cytokines that could damage sperm. 1 In this respect, testicular sperm may be the best candidate to inject into oocytes, because testicular sperm are protected by the testis-blood barrier. Iwahata et al have shown that the period of the injury is one of the prognostic factors for conventional testicular sperm extraction (C-TESE) or microdissection testicular sperm extraction (micro-TESE).…”
Section: Editorial Comment Editorial Comment From Dr Kanto To Testicumentioning
confidence: 99%